The Influence of Activity Ratio, Profitability, Liquidity, and Solvency on Company Value : (Empirical Study on Industrial Sector Companies Listed on the Indonesia Stock Exchange in 2020-2023) - Rila Yunita; Mukhzarudfa Mukhzarudfa; Muhammad Ridwan (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
This research aims to empirically prove the influence of activity ratios, profitability, liquidity and solvency on company value. Partially and simultaneously. The population in this study is industrial sector companies listed on the Indonesia Stock Exchange in 2020-2023. The sampling method uses a purposive sampling method. The sample in this research was 40 companies over 4 years totaling 160 data, after outlier data the total sample in this research amounted to 140 data. The data analysis technique is descriptive statistics, classic assumption tests, including: (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), multiple linear regression analysis, hypothesis testing (t test, f & R2 test) using SPSS version 26 software. The results of this research partially show that the activity ratio has no effect on company value. Meanwhile, profitability and solvency ratios influence company value. Simultaneously the activity ratio, profitability, liquidity and solvency influence the company value of industrial sector companies listed on the Indonesia Stock Exchange for the 2020-2023 period.